An estimation of level sets for non local KPP equations with delay. (29th January 2019) - Benguria, Rafael D; Solar, Abraham
Abstract: We study the large time asymptotic behavior of the solutions of the linear parabolic equation with delay :, , , and . As an application, we obtain estimates on the measure of level sets of non local KPP-type equations with delay. For this type of nonlinear equation we prove that, in contrast to the classical case, the solution to the initial value problem with data of compact support may not be persistent.